The Positive Relationship between Servant Leadership and Employees' Psychological Health: A Multi-Method Approach. (February 2014) - Rivkin, Wladislaw; Diestel, Stefan; Schmidt, Klaus-Helmut
Servant leadership is thought to encourage socially responsible and moral behaviors. In the present article, we test the positive relationship between servant leadership and employees' psychological health. We argue that servant leadership is positively related to employees' health because servant leaders shape employees' needs and create work environments that fulfill these needs. We examine the proposed relationship of servant leadership (a) competing for variance with different well-known stressors, (b) in multiple samples, (c) at the within- and between-person level, and (d) in relation to long- and short-term indicators of strain. On the basis of this multi-method approach we seek to demonstrate that our results are invariant across different methodological conditions. In Study 1 (N=443), we simultaneously tested the between-person level relationships of servant leadership and job ambiguity to emotional exhaustion and de-personalization as the core symptoms of burnout. In Study 2 (N=75), we simultaneously tested the relationships of person-level servant leadership and day-level emotional dissonance to day-level ego depletion and need for recovery as outcomes. The results of both studies demonstrate that servant leadership is negatively related to strain and accounts for unique variance in short- and long-term indicators of strain over and above that explained by well-known job-stressors. Accordingly, servant leadership can be regarded as an important determinant of employees' psychological health.